Analisis Perputaran Persediaan Barang Dagang Pada Apotek Sumber Farma Bolu Kecamatan Tallunglipu - Biringkanae, Astriwati; Limbongan, Mey Enggane (UKI Toraja Press, 2021)
Analysis of Merchandise Inventory Turnover at Sumber Farma Bolu Pharmacy, Tallunglipu.This research is a quantitative descriptive study that aims to determine the system of recording incoming and outgoing goods at the Sumber Farma Bolu Pharmacy. The types of data used in this research are primary and secondary data. Data collection techniques were carried out by observation, interviews, and documentation.The results of this research are the level of inventory turnover at Sumber Farma Bolu Pharmacy for the type of patent medicine is about 12 times a year and classified as good due to the standard, while for the type of generic medicine is about 9 times a year and the turnover rate below the type of patent medicine. This is due to the accumulation of merchandise in the warehouse and also many merchandise are damaged and can no longer be sold (expire).